AUTOMATION OF THE PROCESS OF ENSURING THE CONFORMITY OF THE OBJECT TO THE “GREEN” CONSTRUCTION STANDARDS - R. A. Zherugov; M. H. Kangezova; A. A. Lapidus (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. Solving the main tasks of designing construction objects in accordance with environmental standards is impossible without computer-aided design and database management systems. The article discusses a part of the software package that will automate the process of ensuring compliance of the object with the standards of "green" construction.Method. The basis of the project development is the criteria of the system of voluntary environmental certification of real estate objects, approved by the order of the Ministry of Natural Resources of Russia, as well as the criteria of LEED standards. For data analysis, the software complex MapInfo was used.Result. The structure of the software product has been developed, which will answer the main questions arising in the design of any building, taking into account the standards of green building. For each category the underlying factors (input data) are the corresponding data for each criterion.Conclusion. The developed software package will provide an opportunity to minimize the impact of a construction object on the environment and increase the energy efficiency of the object under construction. Also, improve the quality of organizational and technological decisions of the construction process, reduce the impact of the construction project on the environment and effectively use resources. Full implementation of the algorithm will make it possible to reduce the time and cost of designing buildings and structures, increase the accuracy of drawing details and structural elements, improve the quality and technical and economic level of the design results, and minimize the costs of manual modeling and testing.